A simple method for lodging resistance evaluation of maize in the field - Yang, Jinsheng; Meng, Xiangzeng; Yang, Shuangyuan; Yang, Jinzhong; Li, Zhaoxia; Yang, Qinglong; Zheng, Peifeng; Shao, Xiwen; Wang, Yongjun; Wang, Lichun (Frontiers in Plant Science, 2023)
The increase of planting density is a dominant approach to taking for high yield of maize. However, the stalks of some varieties are prone to lodging under high-density planting conditions. It is urgent for maize breeding to determine the lodging resistance of maize plants, especially in-situ nondestructive evaluation in the field, and also evaluate the lodging resistance of different varieties under cultivation conditions of high density for increased yields. It is introduced a nondestructive in-situ tester to determine the lodging resistance of maize in the field, which can test the lodging resistance of plants by numerical reading of different angles in this study. The method was used to evaluate the lodging resistance of maize simply, quickly, efficiently and accurately. From 2018 to 2020, a total of 1172 sample plants from 113 maize varieties were detected for the lodging resistance of plants. Among them some varieties were planted at different planting densities, and 829 plants were tested at tasseling stage, milk stage and physiological maturity stage. The statistical results show that the values of wind force on maize plants at the 45º inclination angles (F45) are appropriate to characterize maize lodging resistance in-situ by nondestructive test in the field. According to the F45 value, the maximum lodging resistance Fmax can be inferred. The formula is: Fmax=1.1354 F45 - 0.3358. Therefore, F45 value is the optimal index for evaluating maize lodging resistance nondestructive under field-planting conditions.